CONSUMER PSYCHOLOGY IN TRADE MARKETING: HOW UNDERSTANDING BEHAVIORAL PATTERNS HELPS TO INCREASE SALES - Mamatkulova Shoira Jalolovna (Western European Studies, 2024)
In this article we look at the psychological aspects of trade marketing and their impact on consumer behavior. Through research, we see how basic psychological principles and behavioral patterns help companies increase sales and improve the effectiveness of marketing strategies. Our article is based on an analysis of modern research in the field of consumer psychology, as well as practical examples of successful trade marketing strategies.
Keywords: consumer psychology; trade marketing; behavioral patterns